2021
DOI: 10.1016/j.ultrasmedbio.2021.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Imaging in Newborns, Children and Adolescents Infected with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2): Is There a Realistic Alternative to Lung High-Resolution Computed Tomography (HRCT) and Chest X-Rays? A Systematic Review of the Literature

Abstract: Chest computed tomography (CT) has been frequently used to evaluate patients with potential COVID-19 infection. However, this may be particularly risky for pediatric patients due to high doses of ionizing radiation. We sought to evaluate COVID-19 imaging options in pediatric patients based on published literature. We performed an exhaustive literature review focusing on COVID-19 imaing of pediatric patients. Researcher used “COVID-19”, “SARS-CoV2”, “coronavirus”, “2019-nCoV”, “Wuhan virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 136 publications
(71 reference statements)
12
31
0
Order By: Relevance
“…Following the evaluation of the above-mentioned articles, it can be noted that a small number of studies discusses in depth the ultrasound method as a useful instrument of exploration in COVID-positive newborns, a fact that is also confirmed by Caroselli et al in their review, which found only seven articles about lung ultrasound at newborns, infants, and children with SARS-CoV-2 infection [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Following the evaluation of the above-mentioned articles, it can be noted that a small number of studies discusses in depth the ultrasound method as a useful instrument of exploration in COVID-positive newborns, a fact that is also confirmed by Caroselli et al in their review, which found only seven articles about lung ultrasound at newborns, infants, and children with SARS-CoV-2 infection [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing trend in the use of pulmonary ultrasonography, especially in newborns, as evidenced by the numerous recent articles using this imagistic technique, if we compare with the results obtained by conventional radiography or the CT exam [ 7 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations